The Factors affecting the purchasing decision of the Millenial Muslim Generation - Yuniati Fransisca; Albert Kurniawan Purnomo (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2019)
The purpose of the study is to find out the factors that influence the purchasing decision of millenial Muslim generation toward the halal tourism products of Lombok based on the destination personality, brand attractiveness, and brand awareness. Lombok is the only region in Indonesia that has received the most awards in three categories of twelve categories received by Indonesia at the award ceremony of the World Halal Tourism 2016 in Abu Dhabi, Uni Emirat Arab, as The Wolrd’s Best Halal Beach Resort, The World’s Best Halal Tourism Website, and The World’s Best Halal Honeymoon Destination. Data analysis of the study uses SEM WarPLS 6.0. the research findings show Brand Awareness is the only variable of halal tourism concept that does not influence the purchasing decision toward the halal tourism product of Lombok by millenial Muslim generation. The result of the study is expected to be an additional reference for the effort to develop the halal tourism in Indonesia. Keywords: Millenial Muslim Generation